Health Policy Issues and Priority Research Topics Related to Access and Use of Medicines in Iran: A Qualitative and Consensus Development Study - Arash Rashidian; Fatemeh Soleymani; Nader Jahanmehr (Tehran University of Medical Sciences, 2018)
Background: Access to medicines needs to be fully integrated with health financing, human resource planning, service delivery, information and governance systems. We aimed to explore key themes for the identification of priority policy research questions in the area of access to and use of medicines. Methods: We interviewed a purposeful sample of twenty participants in Iran. The interviewees were selected from diverse stakeholders and the listing comprised of the Ministry of Heath, Departments of Health, Industry, Researchers, Development Partners, Advocates, Clinicians, Pharmacists and Private Providers. Qualitative data was analyzed using the framework approach. We then conducted a nominal group technique meeting to reach consensus on research priorities. Results: Seven themes explain important access to medicine policy and practice issues: health sector organization, health sector pharmaceutical policies, health system financing/ insurance system, drug distribution system in the country, individual, household and community level, health care providers, and policies beyond the health sector. As a result of the consensus development process, 17 research priorities related to access to and use of medicines were identified. Conclusion: The key informant interviews clearly demonstrate that the majority of policy concerns were not addressed. There was a mismatch between the concerns and research, and hence the outcomes of this study can contribute to developing a research agenda for improving access to and appropriate use of medicines.